AUGUSTINUS: POTRET SEJARAWAN MASA PERTENGAHAN DAN KONTRIBUSI BAGI KAJIAN SEJARAH ISLAM - Herawati Herawati (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
The main characteristic of medieval period is Theosentris, churchdomination and feudalistic. In this period, the whole order of society governedentirely by the religion (dogma) or the church. Therefore, reason and rationalityis pressed even silenced so as not contrary to the church. This condition is thenled to the declining of Europe, or better known as the "dark ages". Thiscondition is also colored with complexion of European historiography. Thethemes of the history writing are always associated with religion and churchhistory while the author is the pastor, priest, or nun who once acted as ahistorical actor. Thus the free writing and objective writing are not really therebecause there is no distance between the actor and the history writer. Augustineis a figure of a medieval historian who "represents" all the characters.